2010
DOI: 10.1089/jmf.2009.0119
|View full text |Cite
|
Sign up to set email alerts
|

In VitroEvaluation of the Genotoxic Activity and Apoptosis Induction of the Extracts of Roots and Leaves from the Medicinal PlantCoccoloba mollis(Polygonaceae)

Abstract: Coccoloba mollis (Family Polygonaceae) is a medicinal plant popularly used in cases of memory loss, stress, insomnia, anemia, impaired vision, and sexual impotence, but the scientific literature, to date, lacks studies on the biological effects of this species, particularly with regard to cytotoxicity and induction of DNA damage. The aim of the present study was to assess in vitro (in hepatic HTC cells) ethanolic extracts of the roots and leaves of C. mollis for cytotoxicity, genotoxicity, and induction of apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
1
15
0
1
Order By: Relevance
“…They are used worldwide as self-prescribed home medicines, especially in developing countries, as an aid in basic health care in 60%–80% of the population (Agra et al , 2008). Of late, they have even become a source of compounds for the pharmaceutical industry (Tsuboy et al , 2010; Rispler and Sara, 2011). As bioactive compounds from plants have many biological activities, the appreciable biodiversity among Brazilian plants presents great potential in the development of new drugs for application in the treatment of human diseases (Balbani et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…They are used worldwide as self-prescribed home medicines, especially in developing countries, as an aid in basic health care in 60%–80% of the population (Agra et al , 2008). Of late, they have even become a source of compounds for the pharmaceutical industry (Tsuboy et al , 2010; Rispler and Sara, 2011). As bioactive compounds from plants have many biological activities, the appreciable biodiversity among Brazilian plants presents great potential in the development of new drugs for application in the treatment of human diseases (Balbani et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the extract obtained with the roots of C. mollis is more cytotoxic than that obtained with the leaves, and that the decrease in cell viability observed in the MTT assay was a result, at least in part, of induced apoptosis. Both extracts induced DNA damage at a concentration of 20 μg/mL in the comet assay, but genotoxicity was not detected in any of the treatments carried out in the micronucleus test (TSUBOY, 2009). The aim of the present study was to evaluate the ethanolic extracts of root and leaf for toxicity against Artemia salina (brine shrimp larvae), antioxidant activity and phytochemical content.…”
Section: Introductionmentioning
confidence: 90%
“…The results showed that C. mollis roots extract had higher cytotoxic activity than the resulting extract from the leaves and that the alleviation observed in cell viability in the MTT assay was, at least in part, a result of apoptosis induction. In the comet assay both extracts at a concentration of 20 µg/mL induced DNA damage, but with no genotoxicity detected in the micronucleus test with any of the treatments carried out[21].…”
mentioning
confidence: 88%